A Risk‑benefit Assessment Approach to Selection of Adjuvant Chemotherapy in Elderly Patients with Early Breast Cancer: A Mini Review - Agarwala, Vivek; Choudhary, Neha; Gupta, Sudeep (Indian Journal of Medical and Paediatric Oncology, 2017)
Decision-making regarding the use and selection of adjuvant chemotherapy for breast cancer in elderly patients is challenging due to the presence of age-relatedcomorbidities, frailty, andcompeting causes of mortality. One area, relatively neglected in most guidelines, is the effect ofcompeting causes of mortality on presumed benefit of adjuvant chemotherapy for breast cancer in these patients. This article utilizes a clinical case to illustrate the principles of risk-benefit assessment of adjuvant chemotherapy in elderly patients. We suggest an approach that incorporates validated tools for estimating survival benefits of adjuvant chemotherapy, geriatric assessment, predicting toxicity, and estimating remaining life expectancy without cancer. Integration of all these variables provides a better picture of the possible benefits and harms of adjuvant chemotherapy in this populationcompared to conventional approaches that incorporate tumor-related variables and nonstandard measures of geriatric assessment.
Keywords: Adjuvant chemotherapy; comorbidities; competing causes of mortality; early breast cancer; elderly